Embedding tertiary education in rural communities: building 'warm connections'. Issue 1 (2nd January 2020) - Douglas, J.; Kilpatrick, S.; Katersky Barnes, R.; Alderson, R.; Flittner, N.
ABSTRACT: Pathways to higher education can appear opaque and unattainable to rural adults, despite the affordances provided by modern broadband and increasing provision of university online learning options. This paper describes an innovative partnership model that connects rural adults to university and technical and further education pathways through 'warm connections' developed between staff in rural libraries and 'neighbourhood houses', and people working in university outreach and preparation programmes. Through the Warm Connections project, local staff were provided with training and on campus experiences that equipped them to have conversations with rural people about what university is 'like' and what it takes to get a place in a university course. Rural community staff reported being confident in providing customised front-line information and advice to rural residents and were able to direct enquiries to appropriate people in tertiary institutions. Some staff themselves enrolled in and successfully completed university short courses, providing role models for their communities. The project reduced the socio-economic distance between rural adults and tertiary education. It successfully built social capital networks of 'warm connections' between tertiary institutions and rural communities, although the longevity of those networks will depend on continuing effort by tertiary institutions to maintain and refresh connections.